Prueba in vitro de potencia de cefovecin luego de su conservación a distintas temperaturas - Doxandabarat, X.D. (2020)
Cefovecin is a semisynthetic extended-spectrum antimicrobial for veterinary use that belongs to the third generation cephalosporins. It is sold as a lyophilized powder and, once it is reconstituted, the solution has a 28-day expiration conserved at 4ºC. The objective of the present work was to determine the presence of modifications over time in the antibacterial potency of the reconstituted and stored cefovecin in three different ways: 4ºC, -20ºC and -70ºC. The first three months after reconstitution, the potency of cefovecin was compared between the conserved dilutions at 4 ºC, -20 ºC and -70 ºC; and, for the fourth to twelfth months after reconstitution, it was compared between conserved dilutions at -20ºC and -70 ºC. The in vitro antimicrobial activity of the antibiotic was evaluated by plaque diffusion microbiological assay. The parameters evaluated (R2, slope and ordered at the origin) were not statistically different (P> 0.05) when they were compared for the different conservation temperatures throughout the entire study. It can be concluded that the reconstituted cefovecin did not lose its antibiotic potency when it was subjected to freezing neither during a period of 12 months nor during the 3 months that it was evaluated preserved in the refrigerator.\n